Macrophages : origin, functions and biointervention - Kloc, Malgorzata (Results and problems in cell differentiation, 2017)
This volume gives a state-of-the-art overview on macrophage functions in various invertebrate and vertebrate systems and diseases. It also covers various aspects of macrophage development and formation, behavior and response to nano- and biomaterials, the latter of which have become very important components of modern medicine. Macrophages are evolutionarily conserved phagocytotic cells. In recent years macrophages have emerged as one of the most versatile cells of immune system, which, depending on the milieu and circumstance, participate in development or inhibition of cancer, regeneration, wound healing, inflammation, organ rejection and interaction between mother and a fetus. This book will be of particular interest to researchers working in immunology, cancer research, developmental biology, or related fields.